Comparing Health Literacy in High School Female Students and Their Mothers Regarding Women's Health - Marzieh Saeedi Koupai; Mino Motaghi (Mashhad University of Medical Sciences, 2017)
Methods: the present study is descriptive-analytical with comparative type and the statistical population included 200 secondary female school students and their mothers who were randomly selected. The tool to collect data was a two-part researcher-made questionnaire the first part whereof involved demographic information and the second part includes 41 questions of health literacy about women's health in 5 aspects of menstruation hygiene, nutrition, breast self-examination, body activity, iron deficiency anemia. Reliability and validity of the questionnaire were confirmed and the data were analyzed via SPSS22 software. Results: there was not observed any significant difference in three aspects of menstruation hygiene, nutrition and breast self-examination between mean scores of two female groups and their mothers according to Mann-Whitney instability test (p>0.05); however, there was a significant difference in the aspects of body activities and iron deficiency anomia (p